The Impacts of International Migration on Remaining Household Members : Omnibus Results from a Migration Lottery Program - Gibson, John; McKenzie, David; Stillman, Steven (MIT Press, 2015)
We use a migration lottery program to overcome the double-selectivity problems posed by migration. We compare a wide range of outcomes for the remaining household members of Tongan emigrants with those of members of similar households who were unsuccessful in the lottery, with the policy rules determining which household members can move. Multiple hypothesis testing procedures are used to examine robustness. The overall impact on households left behind is largely negative in terms of resource availability, and both sources of selectivity matter, leading studies that fail to address them adequately to misrepresent the impact of migration on households.